Religious Pluralism and Social Cohesion: Case Study of Interfaith Communities in Central Sulawesi - Fadillah, Nur; Nazarullah, Amitya Amir (Generasi Sains Indonesia, 2025)
Religious pluralism remains a critical concern in multi-religious societies such as Indonesia, where diverse faiths coexist within one national framework. Central Sulawesi presents a distinctive context, having experienced religious conflict, particularly the Poso violence in the late 1990s, followed by sustained peacebuilding efforts. This study examines how interfaith communities in Central Sulawesi interpret and practice pluralism to strengthen social cohesion in post-conflict settings. Using a qualitative case study approach, the research explores the experiences of religious leaders, youth, activists, and community members engaged in interfaith activities. Data collection involved interviews, focus group discussions, participant observation, and document analysis of interfaith programs. Thematic analysis identified key patterns related to tolerance, dialogue, collaboration, and the obstacles to maintaining harmony. The findings show that everyday interfaith encounters help reduce prejudice, build trust, and encourage cooperation, aligning with the principles of the contact hypothesis. Activities such as joint community service, cultural gatherings, and peace forums promote mutual understanding and solidarity. Despite these positive outcomes, challenges persist, including lingering mistrust, unequal access to resources, socio-economic disparities, and exposure to radical narratives. The study concludes that inclusive engagement and supportive policies are essential for transforming religious diversity into sustainable social cohesion.